Effects of Different Levels of Thiamine Diphosphate on In Vitro Methane Reduction and Fermentation Characteristics of Korean Native Cow (Hanwoo) - Seong-Shin Lee; Seong-Uk Jo; Heoyn-Sang Kim; Ji-Soo Wi; Yoo-Kyung Lee; Seong-Dae Lee (Fermentation)
This study investigated the effects of different doses of thiamine diphosphate (ThDP) on methane reduction and fermentation characteristics of Korean native cow (Hanwoo). In vitro trials used ThDP powder at 240, 360, 480, 600, and 720 ppm of substrate, with each sample incubated at 39 °C for 24 and 48 h. After incubation, each sample was analyzed for total gas, methane production, dry matter digestibility, and rumen fermentation characteristics. Mean comparisons were performed using Tukey’s test, with significant differences declared at p < 0.05. Total gas production, methane ratio, and methane production per digested dry matter had a quadratic pattern (p < 0.001), and the 480 ppm treatment had the lowest (p < 0.05) at 24 and 48 h of incubation. Total volatile fatty acid concentration showed no significant difference at 24 h but differed significantly at 48 h (p > 0.05). The concentration of propionate had a quadratic pattern (p < 0.001), and the 480 ppm treatment showed the highest levels compared to the other treatments (p < 0.05) after 24 and 48 h of incubation. In conclusion, ThDP supplementation had a methane inhibition effect. In particular, the methane inhibition effect was most pronounced when ThDP was supplemented at 480 ppm.